Influence of Seaweed Liquid Extracts on Growth, Biochemical and Yield Characteristics of Cyamopsis tetragonolaba (L.) Taub. - N. Vijayanand3*, S. Sivasangari Ramya1, S. Nagaraj2 and (Journal of Phytology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Seaweed liquid extracts of marine alga Stoechospermum marginatum significantly enhanced the growth, biochemical and yield of the cluster plant when treated as soil drench. Seaweed Liquid extracts (SLE) at lower concentration (1.5%) was found to have maximum influence on growth parameters viz., shoot length, root length, fresh weight, dry weight, leaf area and moisture content. Moreover, biochemical parameters such as photosynthetic pigments, protein content, sugars, ascorbic acid and nitrate reductase activity were also enhanced when compared to untreated seedlings. There was also noticeable increase in number of clusters/plant, number of flowers/clusters, pod weight, pod length and number of seeds per pod. Higher concentrations (above 1.5%) were found to show inhibitive effect.